2018
DOI: 10.1039/c7dt04449f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular self-assembly of heterobimetallic complexes: a new N,P-based, selective heteroditopic ligand

Abstract: Pyrimidine-hydrazone and phosphole architectures have been combined to create a new heteroditopic ligand capable of forming heterobimetallic Zn/Pd, Pb/Pd and Cu/Pd complexes in high yielding stepwise or one pot reactions. The catalytic activity of these complexes in Heck coupling and Miyaura borylation reactions was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…However, the Ag1–P1 and Ag2–P2 distances of 3.026(3) and 3.111(3) Å, respectively, are too long to be considered genuine Ag–P bonds. The meridional coordination of the octahedral Zn II ions in 2 to the pym‐, hyz‐ and py‐N donors and the hydroxymethyl arms of L1 is identical to that of the previously studied [Zn L1 (SO 3 CF 3 ) 2 ] complex . Each of the L1 molecules of 2 has a linear shape, due to the rotation of both coordination pockets to their cisoid‐cisoid conformations induced by the coordination of both metal ions by the pym‐N donors.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…However, the Ag1–P1 and Ag2–P2 distances of 3.026(3) and 3.111(3) Å, respectively, are too long to be considered genuine Ag–P bonds. The meridional coordination of the octahedral Zn II ions in 2 to the pym‐, hyz‐ and py‐N donors and the hydroxymethyl arms of L1 is identical to that of the previously studied [Zn L1 (SO 3 CF 3 ) 2 ] complex . Each of the L1 molecules of 2 has a linear shape, due to the rotation of both coordination pockets to their cisoid‐cisoid conformations induced by the coordination of both metal ions by the pym‐N donors.…”
Section: Resultssupporting
confidence: 70%
“…The analysis of the former two complexes by NMR spectroscopy showed that the Ag I ions are bound by the P and hyz‐N donors of the pym‐hyz‐phosphole coordination pocket, while the Zn II and Pb II ions are coordinated by all three N donors of the pym‐hyz‐py pocket and the hydroxymethyl arm (Scheme ). This binding results in the L1 molecules having a bent shape, with cisoid‐cisoid pym‐hyz‐py linkages and transoid‐cisoid pym‐hyz‐phosphole, as seen in the [Ag L1 ] 2 (SO 3 CF 3 ) 2 dimer ( 1 ) and the previously studied [Zn L1 (SO 3 CF 3 ) 2 ] complex . It is reasonable to assume that the binding of the Cu II and Ag I ions in [AgCu L1 (SO 3 CF 3 ) 3 ] is similar to these complexes, based on the studies of previous Cu II ‐containing pym‐hyz based complexes .…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations